ANALISIS EFEKTIVITAS PROGRAM TAHFIDZ AL-QURAN DALAM MEMBENTUK KARAKTER RELIGIUS DAN KEDISIPLINAN SANTRI - Heri Santoso; Zulhanan; Mujib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study evaluates the effectiveness of the Quranic Tahfidz Program at Insan Mulya Boarding School (IMBOS) Pringsewu in improving the spirituality and discipline of students. The background of this study highlights the importance of Islamic character education and the formation of spiritual personality through Quranic memorization, which is integrated with spiritual development. The IMBOS Tahfidz program is designed systematically and integratedly, encompassing all educational activities of students to achieve the stated objectives. A qualitative research method with a case study approach is used to explore the program's implementation in depth. Data collection is carried out through observations of the implementation of talaqqi, muraja'ah, ziyadah, and tasmi' in a small halaqah system, as well as analysis of the tiered evaluation system (daily, weekly, monthly) and the role of musyrif/musyrifah. The focus of observation also includes adequate tahfidz facilities and a conducive religious environment (bi'ah Qur'aniyah). The results of the study indicate that the IMBOS Tahfidz Program is very effective. The students' spiritual growth is evident in their strengthened relationship with Allah SWT, their devotion to worship, and their deepening religious understanding through the integration of memorization (tahfidz) and tafsir studies. Students' discipline also significantly improves, marked by adherence to schedules, good time management, and the development of consistency and independence, all rooted in spiritual awareness and moral responsibility. This program successfully shapes a holistic Quranic personality, where students' spirituality permeates the moral, emotional, and existential dimensions, creating students who are not only disciplined but also possess a high level of moral responsibility.